Self-compassion as a protective factor against adverse consequences of social media use: A scoping review - Deepa Manjanatha; Nicole Pippard; Cinnamon S. Bloss (PLoS ONE, 2025)
Self-compassion has been shown to foster wellbeing and act as a protective factor against the development of psychopathology. Its protective capacity against adverse consequences of social media use, however, is not well understood. Given the increasing use of social media in our daily lives, gaining a nuanced understanding of the relationship between self-compassion and adverse consequences of social media use may be important for building and maintaining healthier online behaviors and spaces. We conducted a systematic scoping review of empirical studies on the relationship between social media use, self-compassion, and wellbeing. We restricted our search to peer-reviewed studies published between January 2010 and October 2024 that were written or translated to English. Thirty studies of 32 independent samples including 11,991 participants were eligible for review. Many of these studies were cross-sectional surveys with majority female participants. Studies generally focused on one of two domains: 1) psychological well-being (e.g., anxiety/depression and resilience); and 2) body image and appearance (e.g., appearance dissatisfaction and comparison). The studies included in this review showed mixed results, with four common themes emerging: 1) There are associations between self-compassion and social media in a variety of populations and contexts; 2) Self-compassion may offer protective benefits in the context of social media use, but the extent and mechanisms remain unclear; 3) Self-compassion-oriented interventions may promote favorable health outcomes, with social-media-based approaches emerging as a promising avenue; and 4) Social media use is measured inconsistently, suggesting a standardized measure, while needed, is lacking. This review revealed a promising role for self-compassion in promoting wellbeing and buffering against the adverse effects of social media usage, while highlighting gaps and limitations of existing research. Future research should prioritize improvement in measurement of social media use and explore individual-level risk and resilience factors in the context of social media exposures and engagement.